The Effect of Transformational Leadership and Organizational Commitment on Employee Performance through Organizational Behavior as Intervening Variables - Limanta, Eva Edina (Universitas Pamulang, 2023)
Digital transformation in the 4.0 revolution era requires companies to develop rapidly. The quality of Human Resources (HR) is one of the main things that need attention to support the development of a company (Widayanto et al., 2021)argues that employee performance needs to be fostered and maintained properly because it has a major impact on the quality of a company. Several variables from previous research that show a relationship with employee performance will be used in this study. These variables include transformational leadership, organizational commitment and organizational behavior as intervening variables. This study took employees of PT IQ Education as research objects with a total sample of 100 employees. The analysis will be carried out using the SEM PLS method to see whether there is an effect of transformational leadership and organizational commitment on employee performance directly or through organizational behavior intervening variables.